PELAKSANAAN PENDIDIKAN MUADALAH PADA PONDOK PESANTREN DI PROVINSI BANTEN - Muslim, M (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
This research aims to identify and find out more about the implementation of the Mudalam Education Unit at Islamic Boarding Schools in Banten Province. The research method was carried out through a qualitative approach with analytical descriptive methods to obtain in-depth information about the research object. The results of this research show that the implementation of the Mudalam Education Unit at Islamic Boarding Schools in Banten Province is very low. This is due to the socialization system not being optimal, the licensing process taking a long time, and the requirements for organizing the Mujadi Education Unit being considered very difficult for Islamic Boarding Schools. Some Islamic boarding schools already provide formal education other than Mujadi, such as MI, MTs and MA, there are also those that provide elementary, middle and high school, so Islamic boarding schools think there is no need to open other formal education like Mujadi. The benefits of Mujadi for Islamic boarding schools are that Islamic boarding schools are given the authority to regulate their own curriculum, process teaching and learning activities without being influenced by government policies, can issue diplomas that are recognized by the government and their alumni can continue to higher levels of education, whether similar or not. such as middle and high schools and universities, both at home and abroad. Those who have received advanced status are given the same rights as other formal education, both in terms of funding, teacher welfare, and student rights provided by the government such as PIP, scholarships and other student rights.